2018
DOI: 10.1002/per.2149
|View full text |Cite
|
Sign up to set email alerts
|

Lead Us (Not) into Temptation: Testing the Motivational Mechanisms Linking Honesty–Humility to Cooperation

Abstract: Over the past decades, there has been considerable interest in individual differences in cooperative behaviour and how these can be explained. Whereas the Honesty–Humility dimension from the HEXACO model of personality has been identified as a consistent predictor of cooperation, the underlying motivational mechanisms of this association have remained unclear—especially given the confound between the temptation to exploit others and the fear of being exploited as motivational drivers of defection in social dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 89 publications
8
34
4
Order By: Relevance
“…For example, drawing on the interpersonal circumplex model (Wiggins, ), Wiltermuth, Tiedens, and Neale () found that complementary dominance (body posture, gesturing, reduced interpersonal distances, and speaking in a loud voice) and submissiveness between actors and partners facilitated information exchange during negotiations, which then led to more successful negotiation outcomes. Similarly, we agree with Hilbig et al () that it is important to learn more about the precise motives that tie personality to specific behaviours in negotiations and motives that underpin the reactions these behaviours trigger in turn. Research of this nature would provide a more thorough test of the hypothesized trait‐activation‐response mechanisms in social interactions.…”
Section: Discussionsupporting
confidence: 91%
“…For example, drawing on the interpersonal circumplex model (Wiggins, ), Wiltermuth, Tiedens, and Neale () found that complementary dominance (body posture, gesturing, reduced interpersonal distances, and speaking in a loud voice) and submissiveness between actors and partners facilitated information exchange during negotiations, which then led to more successful negotiation outcomes. Similarly, we agree with Hilbig et al () that it is important to learn more about the precise motives that tie personality to specific behaviours in negotiations and motives that underpin the reactions these behaviours trigger in turn. Research of this nature would provide a more thorough test of the hypothesized trait‐activation‐response mechanisms in social interactions.…”
Section: Discussionsupporting
confidence: 91%
“…It can be shown formally that a lower degree of conflict of interests provides a greater area of cooperation-the area defined by the combination of social preferences and first-order beliefs for which cooperation is justifiable (Murphy & Ackermann, 2015). Consistent with this, empirical results show that cooperation rates are strongly positively correlated with indices of conflict of interests (Hilbig, Kieslich, Henninger, Thielmann, & Zettler, 2018;Rapoport & Chammah, 1965;Vlaev & Chater, 2006). In other words, games with different indices result in different behaviour.…”
Section: Mixed-motive Gamessupporting
confidence: 71%
“…This model most notably adds an honestyhumility factor and reconfigures variance associated with Big 5 agreeableness and neuroticism. The honestyhumility factor has been shown to be important for understanding a range of criteria especially those within the domains of antisocial/unethical behavior and cooperation (Hilbig, Kieslich, Henninger, Thielmann, & Zettler, 2018;Lee, Ashton, Morrison, Cordery, & Dunlop, 2008).…”
Section: Personality Traitsmentioning
confidence: 99%